Comparative evaluation of immunoassays for anti-spike and anti-nucleocapsid antibodies to SARS-CoV-2 against a commercial surrogate serological viral neutralization test in COVID-19 convalescent samples - Leon, Segundo R. (2023)
Objective: assess five EIA tests aimed to quantify specific antibodies to SARS-CoV-2 and compared to a surrogate viral neutralization for assessing neutralizing antibodies. Methods: We conducted a cross-sectional study during the period from July to October 2020, in which the sera of 96 participants whose ages were between 18 and 65 years were evaluated, all recovered from COVID-19 and obtained between 28 and 212 days after the onset of symptoms. ELISA tests used for testing include measurement of total antibodies (IgG & IgM); IgG antibodies against S protein (IgG S1/S2, IgG S, IgG S-RBD); IgG antibodies against nucleocapsid antigens, and IgM antibodies against S-RBD antigen. Pearson's linear correlation coefficient was used to know the degree of correlation between the values of the viral neutralization antibody titer and the values of the titer level of antibodies evaluated by each of the immunoassays performed. Results: Of 96 participants, 46 were women (48%), with a mean age of 40.8 years. In the surrogate viral neutralization test, 85 samples (89.4%) were positive, and the positive neutralization rate ranged from 30% to 97%. In the correlation analysis to evaluate each of the tests that detect antibodies against the viral neutralization test, a positive correlation is observed in the tests for the detection of IgG antibodies against protein S, while the tests based on the detection of antibodies IgG against the nucleocapsid antigen showed a lower correlation. Conclusions: Correlation analysis between each EIA test against the surrogate viral neutralization test showed better results for IgG antibodies against protein S and this is used to measure immunogenicity at the time of vaccination. This study assures us that serological assays can be used to monitor neutralizing antibody responses.